BS14 First demonstration of a novel experimental model of atherosclerosis. The ex vivo on-ecmo amputated 'living' human limb model. (6th June 2022) - Hartley, Adam; Owen, Samuel; Caga-Anan, Mikhail; Afoke, Jonathan; Shalhoub, Joseph; Hassen, Kimberly; Mason, Justin; Haskard, Dorian; Khamis, Ramzi
Abstract : Introduction: Translational modelling for the study of atherosclerosis has been traditionally centred around the use of small animal models, translating to large animal models prior to first in man studies. We propose to disrupt this paradigm by designing an ex vivo pump perfused 'live' limb model, to enable researchers to study molecular targeting of atherosclerosis. Purpose: To develop and test a novel experimental model of atherosclerosis, based on perfusion of an amputated human limb, to reduce time spent in translational pipelines and reliance on animal preclinical atherosclerotic research. Methods: The novel model consists of taking a freshly amputated limb and incorporating it into an ex-situ ECMO system. A custom-made operating table was designed that facilitates the flow of venous blood back into the circuit. The outflow of the table is connected to an oxygenator and then a pulsatile pump in series. The oxygenator is supplied with a sweep gas of 40% oxygen: air mixture. A parallel circuit warms the system to 37°C using a thermocirculator. The circuit outflow is connected to a cannula that is sutured into the proximal end of an amputated limb artery, which permits the passage of an introducer sheath and guiding catheter for intravascular imaging and x-ray angiography (Figure 1A). The pump is set to provide an output of 15ml per stroke (to represent approximately 10% of clinical stroke volume), with an average pump rate of 70 per minute (equating to a heart rate of 70 beats per minute). Thus, total pump output, or 'cardiac output' to the limb is estimated at 1, 050ml/min. Regular monitoring is performed using arterial blood gas analysis, with correction of pH, oxygenation, haemoglobin, lactate and electrolytes. All participants provided written informed consent, and ethical permission was granted by the Imperial College Healthcare Tissue Bank (REC Wales 17/WA/0161; subcollection CAR_RK_17_070) Results: The model has been successfully performed (n=3), maintaining oxygen saturations >99% for the length of perfusion (up to 6 hours). X-ray angiography (Figure 1B), intravascular ultrasound (Volcano, Phillips) (Figure 1C) and optical coherence tomography (Dragonfly Optis, Abbott) (Figure 1D) was performed. In one limb, indocyanine green, a near-infrared fluorescent probe that localises to atherosclerotic plaque, was injected into the system (2mg/kg) and left to circulate for 90 minutes. The arterial tissue was then dissected (Figure1E), and fluorescence reflectance imaging performed (790nm) on the extracted tissue (Figure 1F). This confirmed indocyanine green uptake in areas of calcific atherosclerotic plaque on intravascular ultrasound and optical coherence tomography. Conclusions: This is the first demonstration of this novel ex vivo on ECMO 'living' limb experimental model of atherosclerosis, showing promise for future use in translational interventional imaging and targeting studies.